Characteristics of electrically evoked auditory brainstem responses in patients with cochlear nerve canal stenosis receiving cochlear implants. (January 2018) - Wang, Zhenxiao; Liu, Yun; Wang, Line; Shen, Xixi; Han, Shuguang; Wang, Wei; Gao, Fenqi; Liang, Wenqi; Peng, Kevin A.
Abstract: Objective: To explore the characteristics of the electrically evoked auditory brainstem responses (EABR) in children with cochlear nerve canal stenosis (CNCs) following cochlear implantation (CI), and the EABR thresholds in children with stenotic versus normal cochlear nerve canals. Method: Sixteen children with profound sensorineural hearing loss were included in this study: 8 with CNCs (CNCs group) and 8 with normal cochlear nerve canals (control group). All children underwent cochlear implantation with full insertion of all electrodes. EABR was performed 6 months postoperatively in both groups. Results: The EABR extraction rate was 100% in children with normal cochlear nerve canals and only 50% in children with CNCs. EABR thresholds were significantly higher in children with CNCs of electrodes No. 11and 22 than in children with normal cochlear nerve canals ( P  < 0.05 for both comparisons). There was no significant difference in EABR thresholds among electrode No. 1, 11 and 22 in CNCs group ( P  > 0.05 for all comparisons); while in the control group, the EABR threshold at electrode No 22 was lower than those at both electrodes No. 11 and 1 ( P  < 0.05 for both comparisons), and the EABR threshold at electrode No. 11 was also lower than that at electrode No. 1 ( P  < 0.05). Conclusion: The EABR thresholds in children with normal cochlear nerve canals vary according to the different locations of electrodes in the cochlea; while in children with CNCs, there was no significant difference among different electrode locations. The EABR thresholds in CNCs children were higher than those of children with normal cochlear nerve canals at electrode 11 and 22.